Peningkatan Regulasi Emosi pada Korban Banjir Jombang - Wiryo Nuryono; Diana Rahmasari; Aghus Sifaq; Tyas Andarini Indarwati (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2022)
Indonesia recently entered the rainy season, causing flooding in several areas, including in Jombang Regency, due to heavy rains. In light of this disaster, various physical and psychological supports are needed. Thus, emotional regulation is an important factor, because flood victims face difficult situations during disasters, ranging from loss of property to the most severe loss of family. This study aims to determine the effectiveness of emotional regulation training for flood victims in the Jombang area before and after the treatment. The subjects involved in this study were victims of the Jombang flood, which consisted of 30 children and 10 adults. The research method used is quantitative with an experimental research design in the form of a pretest-posttest control group design. The data collection method used is by using a questionnaire with an ERQ (Emotional Regulations Questioner) scale. The data analysis technique used is to measure the difference between pretest and posttest. Based on the results of this study, it can be seen that the experimental group that was given the treatment experienced a significant increase in emotional regulation than the control group. This indicates that this training is able to improve emotional regulation for flood victims who experience the psychological impact of the disaster they experienced. Keywords: training, enhacement, regulations of emotions